Detection of Canine Parvovirus in Baghdad city by PCR technique: Ahmed F. Ahmed1 ,Shony M. Odeisho1 ,Zhala A. Karim - Ahmed, Ahmed F. (The Iraqi Journal of Veterinary Medicine, 2012)
Canine parvovirus 2 (CPV2) is a highly contagious and fatal disease of dogs, causingacute hemorrhagic enteritis and myocarditis. In this study different mutant strains of the viruswere characterized by polymerase chain reaction (PCR).The fecal samples from infected dogssuspected for CPV2 infection were collected in a suitable medium. The viral DNA from fecalsamples was extracted using specific kits, PCR were carried out with five different primer,pCPV-2ab and pCPV-2b, to distinguish the strain prevalent in field condition. The primerpCPV-2ab recognized both variant CPV-2a and CPV-2b, whereas the primer pCPV-2brecognized only the variant CPV-2b, using the third primer pCPV to recognize the residualbase pair, enabling the differentiation of CPV-2a variant from CPV-2b in field isolates. Thedifferent PCR products were further analyzed by using gel electrophoresis.